ᵈNisaba za₃-mi₂ (Münster)
xxix, 362 sayfa
Keywords: “The volume collects twenty-three essays in English, Italian, French, and German offered to the Assyriologist Francesco Pomponio (University of Messina) from pupils, friends, and colleagues on the occasion of his 70th birthday. In accordance with his scholarly interests, the contributions in the present volume cover a wide range of topics in the field of Ancient Near Eastern studies and present the edition of new textual sources from third to first millennium BC Mesopotamia” --